2004
DOI: 10.1002/tl.142
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the disciplines: A model for helping students learn disciplinary ways of thinking

Abstract: Using the Decoding the Disciplines model, faculty who are deeply ingrained in their disciplinary research answer a series of questions to understand how students think and learn in their field. The cross-disciplinary nature of the process clarifies the thinking for each discipline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
166
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(169 citation statements)
references
References 9 publications
0
166
0
3
Order By: Relevance
“…It has been shown, however, that such disciplinary orders of discourse are often taken for granted by university lecturers in their teaching (Middendorf & Pace, 2004;Tobias, 1986Tobias, , 1992Tobias, -1993. In this respect, Northedge (2002) believes university lecturers often do not fully appreciate "…the sociocultural groundings of meaning.…”
Section: A Disciplinary Discourse Perspective On University Science Lmentioning
confidence: 99%
“…It has been shown, however, that such disciplinary orders of discourse are often taken for granted by university lecturers in their teaching (Middendorf & Pace, 2004;Tobias, 1986Tobias, , 1992Tobias, -1993. In this respect, Northedge (2002) believes university lecturers often do not fully appreciate "…the sociocultural groundings of meaning.…”
Section: A Disciplinary Discourse Perspective On University Science Lmentioning
confidence: 99%
“…Considerable advances in educational research illustrate the importance of more active learning methods (Fink 2003;Middendorf and Pace 2004) as the current information environment offers new mechanisms for building our pedagogies upon this research base. Our professional accrediting body, the National Association of Schools of Public Affairs and Administration (NASPAA), recognizes this transformation and has recently updated the standards defining quality in Public Affairs Education.…”
Section: Traditional Scholarly Roles and Means Of Communicationmentioning
confidence: 99%
“…Adult learners need situations that interrogate what they know from experience and consider alternative perspectives. They need to experience inherent motivation and assess their own mastery, even while instructors are assessing their learning performance (Middendorf and Pace 2004). From this perspective, students cannot be taught what they need to know.…”
Section: Alternative Roles and Practices To Support Student Learningmentioning
confidence: 99%
“…Bottlenecks, which are areas of the discipline where students can get 'stuck' or 'interrupted' in their learning (Middendorf and Pace 2004;4-5), are typically described in conceptual terms, and the Decoding process was originally designed to help experts unpack their own cognitive processes. Using the Decoding interview technique (Pace and Middendorf 2004), experts are guided to unpack troublesome areas for students, working through how they approach and 'think through' such difficulties as experts.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Decoding interview technique (Pace and Middendorf 2004), experts are guided to unpack troublesome areas for students, working through how they approach and 'think through' such difficulties as experts. However, in our interviews of seven faculty members from four diverse disciplines as described in Chapter 2 of this issue (Miller-Young and Boman), we observed that many of the bottlenecks described had more to do with ways of being-in-theworld, having affective, relational, and identity elements.…”
Section: Introductionmentioning
confidence: 99%